HOW VIDEO GAMES WROTE THE FUTURE. - HOSKIN, PETER (Prospect, 2025)
The article discusses how video games became the driving force behind artificial intelligence (AI). Topics discussed include AI in the game "Half-Life," career background of Demis Hassabis, one of the greatest practitioners of AI who began in the video-game industry and implications of an AI model called AlphaFold that can predict the structures of protein molecules.